Potent Bidirectional Cross-Talk Between Plasmacytoid Dendritic Cells and γδT Cells Through BTN3A, Type I/II IFNs and Immune Checkpoints - Girard, Pauline; Ponsard, Benedicte; Charles, Julie; Chaperot, Laurence; Aspord, Caroline (Frontiers in Immunology, 2020)
Plasmacytoid DCs (pDCs) and γδT cells are both critical players in immunosurveillance against pathogens and cancer due to their ability to sense microbes and cell stress through recognition of pathogen-associated molecular patterns or altered metabolism (phosphoantigens (PAgs)). Their unique features, high functional plasticity and ability to interact with many immune cell types allow them to bridge innate and adaptive immunity, initiating and orientating widely immune responses, hence contributing to protective and pathogenic immune responses. Yet, despite strategic and closed missions, potential interactions between pDCs and γδT cells are still unknown. Here we investigated whether there is interplay between pDCs and γδT cells and the underlying molecular mechanisms. Purified human pDCs and γδT cells were cocultured in presence of TLR-L, PAg and zoledronate (Zol) to mimic both infectious and tumor settings. We demonstrated that TLR7/9L- or Zol-stimulated pDCs drive potent γδT-cell activation, Th1 cytokine secretion and cytotoxic activity. Conversely PAg-activated γδT cells trigger pDC phenotypic changes and functional activities. We provided evidence that pDCs and γδT cells cross-regulate each other through soluble factors and cell-cell contacts, especially type I/II IFNs and BTN3A. Such interplay could be modulated by blocking selective immune checkpoints. Our study highlighted crucial bidirectional interactions between these key potent immune players. The exploitation of pDC-γδT cells interplay represents a promising opportunity to design novel immunotherapeutic strategies and restore appropriate immune responses in cancers, infections and autoimmune diseases.